2020
DOI: 10.1371/journal.pone.0228661
|View full text |Cite
|
Sign up to set email alerts
|

Association between habitual use of coping strategies and posttraumatic stress symptoms in a non-clinical sample of college students: A Bayesian approach

Abstract: The present study investigated the influences of coping styles on posttraumatic stress symptoms (PTSS) among a sample of non-clinical college students who were exposed to traumatic events. Ninety-nine college students participated in the study. However, the sample used in the analyses consisted of only 37 participants who fulfilled the DSM-IV criterion A for Posttraumatic Stress Disorder (PTSD) diagnosis. The PTSD Checklist-Civilian Version (PCL-C) and the Brief COPE were used to assess the participants' PTSS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 64 publications
1
19
0
3
Order By: Relevance
“…Past research has also showed that coping is an important factor in contributing psychosocial and physical health of individuals (Yıldırım 2019 ). Individuals high in adaptive coping strategies experience less depression (Erickson and Feldstein, 2007 ), anxiety (Brouzos et al 2020 ), and stress (Viana Machado et al 2020 ) and greater psychological well-being (Mayordomo et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has also showed that coping is an important factor in contributing psychosocial and physical health of individuals (Yıldırım 2019 ). Individuals high in adaptive coping strategies experience less depression (Erickson and Feldstein, 2007 ), anxiety (Brouzos et al 2020 ), and stress (Viana Machado et al 2020 ) and greater psychological well-being (Mayordomo et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive coping (i.e. problems-focused and positive reappraisal coping strategies) has been found to be negatively related with depressive symptoms (Erickson & Feldstein 2007 ), anxiety (Brouzos et al 2020 ), and stress (Viana Machado et al 2020 ). Maladaptive coping strategies (i.e.…”
Section: Mediating Effect Of Copingmentioning
confidence: 99%
“…The emotion-focused coping dimension included emotional support, religion, positive reframing, acceptance, and humor. The dysfunctional coping dimension included self-blame, venting, denial, self-distraction, behavioral disengagement, and substance use [ 28 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…For our distraction code, we used the definition applied by Ng and colleagues (2016). Although Ng and colleagues (2016) categorized distraction as an EBP, distraction is highly heterogeneous, and other scholars have conceptualized distraction as maladaptive or dysfunctional (e.g., Machado et al, 2020). Therefore, we perform one set of analyses with distraction as an EBP and one set with distraction as a non-EBP.…”
Section: Selection Of Ebp Codesmentioning
confidence: 99%